First data of Iberian Nematomorpha, with redescription of Gordius aquaticus Linnaeus, G. plicatulus Heinze, Gordionus wolterstorffii (Camerano) and Paragordius tricuspidatus (Dufour) - Villalobos, Leonor Cristina de (2001)
Four species of Nematomorpha are recorded from NE Spain, representing the first reliable data on the group in the Iberian peninsula. Gordius aquaticits Linnaeus, 1758, G. plicatulus Heinze, 1937, Gordionus wolterstorffii (Camerano, 1888) and Paragordius tricuspidatus (Dufour, 1828) are redescribed based on scanning electron microscope observations. Notes on intraspecific morphological variation and ecology of the species are given.